Low-Dose Taxol Promotes Neuronal Axons Extension and Functional Recovery after Spinal Cord Injury - Baoguo Liu; Sumei Liu; Dejun Sun (Mediators of Inflammation)
Axonal regeneration has been the research focus in the field of clinical treatment for spinal cord injury (SCI). The growth and extension of neuronal axons is a dynamic biological process mediated by the cytoskeleton, and microtubule plays an important role in axonal growth. Moderate stabilization of microtubule promotes axonal growth and eliminates various intra- and extracellular mechanisms that impede axonal regeneration. After SCI, the damaged axons rapidly form a growth cone, wherein the stability of tubulin decreases, impairing axonal regeneration. Taxol with proven clinical safety is commonly used as a broad-spectrum antitumor drug. Importantly, Taxol can promote axonal extension by enhancing and stabilizing the microtubule assembly. In our study, we systematically investigated the differentiation of neural stem cells (NSCs) in vitro and functional recovery in injured rats in vivo following Taxol treatment. Low-dose Taxol promoted differentiation of NSCs to neurons and significantly extended the axons in vitro. In vivo, Taxol promoted the expression of βIII-tubulin in the injured areas and motor function recovery after SCI. Low-dose Taxol is a promising clinical agent to promote axonal regeneration after SCI.